IMPROVEMENT OF THE DEGREE PROFESSIONAL TRAINING SYSTEM FOR PENITENTIARY STAFF: EXPERIENCE OF UKRAINE AND USA - Вікторія Аніщенко (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2023)
Reformation of the penitentiary system of Ukraine requires an increase of requirements for the quality of staff training of the penitentiary institutions, detention centers, camps for holding prisoners of war and probation bodies. It is necessary to state that the implementation of the tasks of the state criminal and legal policy is impossible without studying the leading foreign practices in the field of training of penitentiary staff, since the level of society's security depends on the level of their professional competence. The study of the training system of penitentiary staff  in the USA is relevant for Ukraine. The USA remains the flagship in the development of the theory and practice of the democratic development of the penitentiary system and has a clearly formed structural and logical system of their training. Therefore, the purpose of the study was to conduct a comparative analysis of the professional training system of penitentiary staff in Ukraine and the USA and to determine on this basis the pedagogical conditions for the formation and improvement of their professional competence. The results of the study proved that the realities of the quality of the staff professional activity of the State Criminal and Executive Service of Ukraine, the system of degree professional training of penitentiary staff need improvement. During the study, the main directions for improving the process of penitentiary staff  training were identified, namely: creating an innovative educational environment, updating the content of educational programs and introducing innovative educational technologies, providing pedagogical conditions for the modern professional competencies complex formation of penitentiary staff, revising the terms of their training and improving their qualifications depending from the type of official and professional activity. Proposed pedagogical conditions, among which the most important are the professional orientation of the training content of penitentiary staff taking into account the specifics and profile of professional activity based on selection criteria, the combination of theoretical training with the acquisition of skills and abilities of their use in accordance with professional tasks with the help of certain interactive training methods, internship during education, will provide an opportunity to form the modern professional competence of the State Criminal and Executive Service of Ukraine staff. Further study of foreign experience in the training of penitentiary staff will contribute to the development of an effective model of penitentiary staff training and will bring it closer to the requirements of international standards.